Usage of telecommunication technology in perpetration of sexual assault- A study conducted on reported victims in a Tertiary Medical College Hospital OCC (Community Based Medical Journal, 2021)
The sexual assaults and its consequences are increasing along with socioeconomic development of the country. Rise of modern communication technology add fuel to the flame. This descriptive cross-sectional study aimed to evaluate the role of communication technology in sexual assaults in Bangladesh. There were 87 victims included in this study. All were female of 6 years to 40 years of age, mean age was 15.67 (± 6.69) year. Most of the victims were below 20 years of age and came from low income families. About 76% mobile used were smart phone. Among them 46% were owned by the victims herself, 26% gifted by the assailants to the victims. Talking through mobile (37%) was the main communication route between the assailants and the victims; followed by direct verbal (31%), mixed verbal and mobile talking (26%) and others (6%). Regarding methods of communication, they only talk in 42% cases and 36% cases used mixed method (talking, SMS and video chatting). The assailant paid all the costs in 62% cases. Mobile phone came as a blessing in communication, but inchoate use makes it a curse to our society. Parents should be cautious about their children's mobile usage (especially smart phone) daily. Government also should make some policy on using mobile technology by the younger citizens.CBMJ 2020 July: Vol. 09 No. 02 P: 03-07